2021
DOI: 10.1101/2020.12.31.424963
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HOPMA: Boosting protein functional dynamics with colored contact maps

Abstract: In light of the recent very rapid progress in protein structure prediction, accessing the multitude of functional protein states is becoming more central than ever before. Indeed, proteins are flexible macromolecules, and they often perform their function by switching between different conformations. However, high-resolution experimental techniques such as X-ray crystallography and cryogenic electron microscopy can catch relatively few protein functional states. Many others are only accessible under physiologi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 109 publications
0
3
0
Order By: Relevance
“…This field has now established a fruitful dialog with novel experimental techniques (26) and is contributing to the goal of structural ensemble determination (27), benefiting from innovative techniques such as cryo-electron microscopy (cryo-EM) tightly coupled with computational modeling (28). Applications of ENM in this context include high resolution modeling of cryo-EM structures (28), protein-protein docking (29), protein-ligand docking at allosteric ligand binding sites (30), and extensive and fast exploration of the conformational space to discover new potentially functional sites (31).…”
Section: Introductionmentioning
confidence: 99%
“…This field has now established a fruitful dialog with novel experimental techniques (26) and is contributing to the goal of structural ensemble determination (27), benefiting from innovative techniques such as cryo-electron microscopy (cryo-EM) tightly coupled with computational modeling (28). Applications of ENM in this context include high resolution modeling of cryo-EM structures (28), protein-protein docking (29), protein-ligand docking at allosteric ligand binding sites (30), and extensive and fast exploration of the conformational space to discover new potentially functional sites (31).…”
Section: Introductionmentioning
confidence: 99%
“…NMA determines low-frequency motions at a very low computational cost and these are particularly interesting to the structural biology community because they give insight into protein function and dynamics. On our side, we have proposed a computationally efficient nonlinear NMA method that can be applied to largest complexes from the Protein Data Bank (PDB), and which also very well preserves local stereochemistry [3][4][5].…”
mentioning
confidence: 99%
“…Recently, we have shown that it can be extended to model local deformations and to better preserve the stereochemistry of the protein. We have developed a computationally efficient nonlinear NMA method that can be applied to the largest complexes from the Protein Data Bank (PDB) [3][4][5].…”
mentioning
confidence: 99%